The Effect of the Method of Airway Management During Endoscopic Sinus Surgery Procedures on the Intraoperative Bleeding - Pavlov, V. E.; Polushin, Yu. S.; Kolotilov, L. V.; Karpishchenko, S. A. (Vestnik anesteziologii i reanimatologii, 2022)
The objective : to conduct a comparative assessment of the severity of intraoperative bleeding with different methods of airway management (using a laryngeal mask and endotracheal tube) during endoscopic rhinosinussurgical procedures. Subjects and Methods . A prospective randomized cohort single-center study of 160 cases of endoscopic rhinosinussurgical procedures under general anesthesia was conducted.Tracheal intubation (TI) was used in 79 cases (Group 1), a laryngeal mask (LM) – in 81 (Group 2). The evaluation criteria in the groups included the bleeding intensity (BI) by 6-point scale of average categories (Fromme-Boezaart Score), indicators characterizing the state of blood circulation during surgery: HR, BPsys., BPdiast., MAP, and perfusion index. Results . Significantly lower BI values were observed in Group 2 at all time points of the study (at the 10th, 30th and 60th minute of surgery). This was due both to using a laryngeal mask, and to lower HR, BPsys., BPdiast, and MAP. Conclusion . The use of a laryngeal mask for airway management during general anesthesia in endoscopic rhinosinussurgical procedures helps to reduce the intensity of surgical field bleeding.